Comparative Study of Antioxidant Activity of Flower of Aloe vera and Leaf Extract of Aloe ferox - Shah Muhammad Haroon; Sammia Shahid; Syed Ammar Hussain; Hamid Raza (Journal of Basic & Applied Sciences, 2018)
Great attention has been focused on medicinal plants and phytoconstituents due to their free radicals scavenging tendency. The present study investigates the comparative antioxidant ability of aqueous extracts of flower of Aloe vera and leaf of Aloe ferox. Antioxidant activity was assessed by using the DPPH, FRAP and ABTS+ free-radical method. The IC50 values of aqueous extracts of flower of the A. vera and leaf of A. ferox in DPPH assay were 406.04 and 517.01 µg/ml, in ABTS+ radical scavenging assay were 44.72 and 173.05 µg/ml, EC1 in FRAP assay were 0.28 and 0.51 (mg/ml) respectively. Results of the present study showed that antioxidant capacity of whole leaf of Aloe ferox Mill was significantly higher than Aloe vera flowers.